Ecofeminist Ethics Utopic Conversations - Eaton, Heather 1956- (2000)
Within and underlying the spectrum of ecofeminist discourses, there are assumptions about ethical aims and moral norms which propel the critique and undergird the visions for an alternative future. Ecofeminists are situated in the crevasse between the ‘is’ and the ‘ought’. Some seek to glean ethics from the ‘is’, at times in the form of case studies. One purpose for this is to deduce ethical systems and worldviews from the specific conditions of ‘what works’, which then allows for a connection across the crevasse. Nonetheless, the bulk of ecofeminist efforts is, customarily, perched on the ridge of the ‘ought’—critiquing, exploring, denouncing, affirming and creating ethical possibilities and opportunities—developing transformative and emancipatory paradigms.
Keywords: ecofeminist